Cortisol and proinflammatory cytokine profiles in type 1 (reversal) reactions of leprosy - Chaitanya, V.S.; Lavania, M.; Nigam, A.; Turankar, R.P.; Singh, I.; Horo, I.; Sengupta, U.; Jadhav, R.S. (Immunology letters, 2013)
•We observed localized under expression of 11 β HSD I mRNA in leprosy cases with T1R.•We observed localized under expression of 11 β HSD II mRNA in leprosy cases with T1R.•We identified low lesional and urinary cortisol levels in leprosy cases with T1R.•We observed negative correlation between serum cortisol and IP-10 in both T1R and NR cases.•We observed negative correlation between serum cortisol and TNF-α in both T1R and NR cases. Cortisol levels in the circulation and at the sites of peripheral inflammation regulate type 1 (Reversal) reactions in leprosy akin to delayed type hypersensitivity reactions (DTH). In this study we determine the extent to which the differential mRNA expression of genes encoding cortisone–cortisol shuttle enzymes (11 β hydroxysteriod dehydrogenase I & II (11 β HSD I & II)), circulatory levels of proinflammatory cytokines (IL-6, IL-7, IP-10, IL-17F, IL-23, TNF-α, IL-1β, PDGF BB and CRP) and cortisol are associated with development of type 1 reactions in leprosy. Urine, blood and incisional skin biopsy samples from site of lesions were collected from 49 newly diagnosed untreated leprosy cases in T1R and 51 cases not in reaction (NR). mRNA expression levels of genes encoding 11 β HSD I & II in skin biopsy samples were determined by realtime PCR. Cortisol levels from the lesional skin biopsies, serum and urine samples and serum proinflammatory cytokine levels were measured using ELISA. The mean expression ratios of 11 β HSD I & II are significantly lower in leprosy cases with T1R when compared to the NR leprosy cases. Cortisol levels in lesional skin biopsies and in urine are significantly lower (p=0.001) in leprosy cases with T1R. Serum cytokine levels of IP-10, IL-17F, IL-IL-6 and TNF-α are significantly higher (p<0.05) in leprosy cases with T1R when compared the NR leprosy cases. Our study indicated an association of urinary and lesional skin cortisol levels with the manifestation of T1R in leprosy. IP-10, IL-17F, IL-6 and TNF-α can be potential prognostic serological markers and gene expression markers for early detection of type 1 reactions in leprosy.